TATA KELOLA DAN EFISIENSI LAYANAN PELABUHAN LAUT: IMPLIKASI HUKUM PEMBAGIAN KEWENANGAN BERDASARKAN UU NOMOR 6 TAHUN 2023 TENTANG CIPTA KERJA - Syamsul Rijal; Adhe Ismail Ananda (Journal Publicuho, 2025)
Seaports play a strategic role as logistics hubs and drivers of national economic growth. However, port governance in Indonesia continues to face structural challenges, particularly regarding the distribution of authority between Port Authorities (OP) and Port Business Entities (BUP). Regulatory reform through Law No. 6 of 2023 on Job Creation amended key provisions of Law No. 17 of 2008 on Shipping by explicitly separating the functions of regulator and operator. This study aims to analyse the legal implications of such authority distribution on the efficiency of seaport services in Indonesia. A normative-juridical approach is employed by examining Article 110A and related provisions in the Job Creation Law. The findings indicate that while the legal reform intends to enhance efficiency and attract investment, its implementation is hindered by regulatory disharmony, overlapping authority, and weak institutional coordination. Therefore, regulatory harmonisation and institutional governance strengthening are essential to achieving sustainable port service effectiveness.